Tadeusz Jan Łopuszański i dzieło jego życia, red. Z. T. Wierzbicki i in. Warszawa 1995, Fundacja im. Tadeusza Łopuszańskiego, ss. 101 - Gulczyńska, Justyna (Biuletyn Historii Wychowania, 1996)
Tadeusz Jan Łopuszański i dzieło jego życia, red. Z. T. Wierzbicki i in. Warszawa 1995, Fundacja im. Tadeusza Łopuszańskiego, ss. 101